Attitude toward virginity and its determinants among girls in Tabriz: Iran - Somayyeh Naghizadeh; Raziyeh Maasoumi; Mojgan Mirghafourvand; Farideh Khalajabadi-Farahani (BMC, 2024)
Abstract Background We aimed to assess the attitude of unmarried girls towards virginity, and its determinants, comparing three age cohorts (born in the 70s, 80s, and 90s) in the city of Tabriz in northwestern Iran. Methods We conducted a cross-sectional survey among 700 girls residing in Tabriz in 2021 employing a population-based cluster sampling based on health clinics and households. We collected data using a pilot-tested instrument, which comprised socio-demographic questions, and statements to assess attitudes towards virginity and its importance, the meaning of virginity, ways of losing virginity, and perception of the hymen. The data was analyzed using SPSS, version 21. Analysis of variance and independent t-test was used for bivariate analysis and linear regression was used to identify the determinants of the attitude. A p value under 0.05 was considered statistically significant. Results Only about one-third (35.2%) of unmarried girls considered preserving virginity as an important issue for girls before marriage in current days. About 27% were uncertain and about 38% believed it was unimportant. The importance of virginity (score range 7-35) was significantly greater for girls born in the 70s than for girls born in the 80s and 90s (p < 0.05). In the multivariate linear regression model, the determinants of the importance of virginity were older age, greater religious affiliation, living with both parents and lower consumption of the internet and social networks for sexual information. Conclusions This study indicates significant shifts in sexual attitudes among young females which may have important implications for marriage age and the culturally and age-appropriate sexual health interventions of young people.